Rebuilding Public Trust in Islamic Banking Through the Utilization of Technology: Conceptual Review and Strategies - Antasari, Novira Dian; Zulhamdani; Amat Basri; Triana Salma Dewi (Tech-E, 2025)
Public trust in Islamic banking has been a significant challenge in recent years. This is influenced by several factors such as lack of technology literature, technology distribution, cybersecurity, regulatory frameworks, customer awareness, and financial inclusion. This research aims to highlight the technology in restoring public trust in Islamic banking and present practical strategies for digital Sharia banks. This research aims to identify public trust in Islamic banking in Indonesia through technology. This research design is descriptive qualitative and the type of data used is secondary data. Sources and data were obtained from OJK websites, books, the internet, social media, journals, and other relevant digital format. Data is processed using the Python programming language. The results of this research indicate that digital literacy for Bank Hijra is less well-known among the public. From the mobile banking application, the rating of the sample banks shows a number above 4. User reviews show that the use of these applications has not yet achieved maximum customer satisfaction, as there are still complaints about data security concerns. It concluded that customer trust in digital Sharia banks has indeed increased, but there is still a need to improve data security and digital literacy, and user experience for the public.